The Effect of the Application of Aloe Vera Gel Compresses on Breast Swelling Pain in Postpartum Mothers at Sumber Waras Hospital - Obehetan, Irivin Lesli Yunita (Jurnal Kesehatan STIKes Sumber Waras, 2026)
Breast engorgement is a common problem among postpartum mothers that often causes pain, disrupts comfort, and interferes with the success of exclusive breastfeeding. Non-pharmacological management using aloe vera gel compresses is believed to help reduce pain due to its active compounds with analgesic and anti-inflammatory properties. This study aimed to determine the effect of aloe vera gel compresses on breast engorgement pain in postpartum mothers at Sumber Waras Hospital in 2025. The study employed a pre-experimental one-group pretest–posttest design. The sample consisted of 10 postpartum mothers selected through purposive sampling. Pain intensity was measured using the Numeric Rating Scale (NRS), and data were analyzed using a dependent t-test. The results showed a decrease in the mean pain score after the application of aloe vera gel compresses: from 4 to 3 on the first day, from 3 to 2.10 on the second day, and from 2.20 to 1 on the third day. Statistical analysis revealed a p-value < 0.05 on all treatment days, indicating a significant effect of aloe vera gel compresses in reducing breast engorgement pain. In conclusion, aloe vera gel compresses are effective in reducing breast engorgement pain in postpartum mothers. This intervention can be applied as a safe, inexpensive, and practical non-pharmacological therapy to support the success of exclusive breastfeeding